Assessing the Radiographic Position of the Mental Forament in a Brazillian Population - Pasquali, Jordan Gasparetto; Narazaki, Nathan Dyoji; Franco, Ademir; Vieira, Iran; de Lima, Antonio Adilson Soares; Fernandes, Ângela (Journal of Dentistry Indonesia, 2017)
The mental foramen is a clinically important landmark for several clinical dental procedures. The aim of this study is to assess the anatomic position of the mental foramen (MF) in panoramic radiographs of a Brazilian population. The sample consisted of 2,100 panoramic radiographs, obtained from 8,600 clinical files from the School of Dentistry at the Universidade Federal do Paraná. Two calibrated examiners investigated the MF according to the classification of Tebo and Telford, which locates the right and left MF into 6 different positions in relation to the apex of the adjacent teeth. Results: The MFs were similarly distributed between the apices of the mandibular premolars (class III) and below the apex of the mandibular second premolar (class IV). More specifically, on the right side 41.8% (n = 878) of the MFs were classified as class III, while 47.52% (n = 998) were classified as class IV. On the left side 42.47% (n = 892) were classified as class III, while 47.38% (n = 995) were classified as class IV. The results indicate that MFs are often located adjacent to the apex of the mandibular second premolar. However, slight variations may occur in the positioning of the MF to the mesial direction. Clinicians and surgeons must be aware of the position of the MF and its potential variations prior to anaesthetics and surgical procedures in the mandible.